Effect of TANFAC Effluent on varietal response of Black gram (Vigna mungo L. Hepper) - D. Arulbalachandran, S. Dhanam (Journal of Phytology, 2009)
The present research work has been carried out to understand the effect of different concentrations of TANFAC effluent on seed germination and seedling growth of five varieties of black gram (Vigna mungo (L.) Hepper). The Increasing pace of industrialization in public and private sectors along with urbanization, population explosion and green revolution are reflected in varying degree of pollution of air, water, and soil. The TANFAC effluent is having a higher amount of organic and inorganic element. The Physico-chemical analysis showed that it was acidic in nature. It was rich in total suspended and dissolved solids with large amount of Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). The effluents severally affect crop plants and soil properties when used for irrigation. The growth parameters such as germination percentage root length shoot length, number of lateral roots, fresh weight and dry weight were taken on 10th day. All the parameters were found to increase at 10% effluent concentration and it decrease from 25% effluent concentration onwards. Among black gram, variety V-2 was tolerant to TANFAC effluent when compared to other varieties.